ナンキョク エンダービーランド アムンゼン ワン ニ オケル アデリーペンギン ノ シュウダン ノ ブンプ ト ハンショク スウ - 高橋, 晃周; タカハシ, アキノリ; 佐藤, 克文; サトウ, カツフミ; 西川, 淳; ニシカワ, ジュン; 河野, 通治; コウノ, ミチハル; 内藤, 靖彦; ナイトウ, ヤスヒコ; Takahashi, Akinori; Sato, Katsufumi; et al. (2000)
P(論文) アデリーペンギンの集団繁殖地の分布および繁殖数の調査を, 1998年12月23日, エンダービーランド・アムンゼン湾において, ヘリコプターをもちいて行った。これまでに報告されていた1ヵ所に加え, 新たに3ヵ所の集団繁殖地を発見した。これら4繁殖地でのアデリーペンギンの繁殖数の合計はおよそ9760ペアで, アムンゼン湾の繁殖個体群は東エンダービーランドにおける最大規模の繁殖個体群であることが明らかになった。 Adelie penguin colonies were surveyed throughout ice-free areas in Amundsen Bay, Enderby Land, from a helicopter on 23 December 1998. The locality and number of breeding pairs of three newly discovered colonies, in addition to a known colony are described. In total, about 9760 pairs of Adelie penguins breed in the four colonies in this region, comprising one of the largest breeding populations in eastern Enderby Land. departmental bulletin paper